Interpreting gender gap issues in standardized tests: definition and application of a theoretical tool - Spagnolo, Camilla; Nicchiotti, Bianca (Frontiers in Education, 2023)
Gender gap in STEM disciplines is a phenomenon that has been extensively studied and described. In this paper we focus on the gender gap in mathematics and firstly we illustrate the international and national situation that emerges from the reports of large-scale assessment. The core of our work then is the definition and explanation of the gender gap index 𝐺𝐺𝐼 𝑘 , a theoretical tool which allows us to categorize the results of each item in terms of the resulting gender gap. Lastly, the index is used to analyze some items taken from INVALSI tests and it is compared and contrasted with other indexes commonly used, in order to give an example of its possible use in research in mathematics education.1 From an international perspective, OECD and IEA are working on large-scale assessment. Both OECD and IEA have a range of different programmes and flagship studies about education (respectively CELE LEEP, CERI, PAI, PIAAC, PISA, TALIS and TIMSS, PIRLS, ICCS, ICILS, REDS, LaNA. The ones dealing with mathematics achievements are PISA, developed by OECD (https://www.oecd.org/pisa/) and TIMSS, conducted by IEA (https://www.iea.nl/studies/iea/timss).